Binding of per- and polyfluoroalkyl substances (PFASs) by organic soil materials with different structural composition – Charge- and concentration-dependent sorption behavior. (June 2022) - Campos-Pereira, Hugo; Makselon, Jennifer; Kleja, Dan B.; Prater, Isabel; Kögel-Knabner, Ingrid; Ahrens, Lutz; Gustafsson, Jon Petter
Abstract: The charge- and concentration-dependent sorption behavior of a range of per- and polyfluoroalkyl substances (PFASs) was studied for three organic soil samples with different organic matter quality, one Spodosol Oe horizon (Mor Oe) and two Sphagnum peats with different degrees of decomposition (Peat Oi and Peat Oe). Sorption to the two peat materials was, on average, four times stronger compared to that onto the Mor Oe material. In particular, longer-chained PFASs were more strongly bound by the two peats as compared to the Mor Oe sample. The combined results of batch sorption experiments and 13 C NMR spectroscopy suggested sorption to be positively related to the content of carbohydrates (i.e., O-alkyl carbon). Sorption of all PFAS subclasses was inversely related to the pH value in all soils, with the largest pH effects being observed for perfluoroalkyl carboxylates (PFCAs) with C10 and C11 perfluorocarbon chain lengths. Experimentally determined sorption isotherms onto the poorly humified Peat Oi did not deviate significantly from linearity for most substances, while for the Mor Oe horizon, sorption nonlinearity was generally more pronounced. This work should prove useful in assessing PFAS sorption and leaching in organic soil horizons within environmental risk assessment. Graphical abstract: Image 1 Highlights: Sorption to Sphagnum peat was generally stronger than to Spodosol Oe soil. Sorption pH dependency increased with perfluorocarbon chain length up to C10 . 13 C NMR spectroscopy suggested sorption contributions from carbohydrates (O-alkyls). Sorption non-linearity was more pronounced onto Spodosol Oe material.